PSYCHOSEMANTIC METHODSIN PSYCHOLOGICAL STUDY OF CONSCIOUSNESS - Дробот, О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
In the sphereof psychological study of consciousness, the matter of valid psychological instruments is a very contemporary problem which remains virtually open. Today, the study of individual structures of meaning sinconscious nessis view edinthedirection of psychosemantic studies, and therefore, definition of a complex of psychosemantic methods allowing to determine the meaning and structure of any consciousness type becomes the task of contemporary psychology. This article show sthat psychosemantics, a science originating from cognitive psychology is a field of study of the human’s subjective world. A description and substantiation of use of the following group of methods was provided. The method of verbal semantic differential – Semantic Differential (SD), a method of building individual or group semantic spaces was developed by American scientists under the leadership of Charles E. Osgood.The method of personalconstructs – the repertory gridtechnique developed by George Kelly allows to reconstruct the vision of the world in the subject’s eyes. Kelly defines personal constructs as a system of binary oppositions used by a subject for categorization of self and other people.The associative method, featuring analysis of psychological nature of processes lying at the core of associations. The method of visual semantic differential (SD), O.Y. Artemieva’smethodofpartiallycontrolledsemantizationallowstoregistermanifestations of visual semantics, showing the attitude toward plotless geometric images. Theprojectivemethod, J. Sax’sandS. Levis’sUnfinishedSentencestechnique; aversionofthistechniquewhichwemodifiedwas used to study professionalconsciousness of managers. The upsides and downsides of each method were described. Aconclusion wasdrawnregardingtherelevance of the psychosemantic complex of methods presented here to the objective of psychological study of the meaning and structure of consciousness.